Trends in information and communication systems for automobiles. (4th August 2014) - Fujii, Haruki; Koide, Kouhei
With the advance of the information society, the use of automobiles is diversifying. The increasing diversification and availability of means of communication has been accelerating the trend towards incorporating automobiles in business and daily life, and the enactment in Japan of the Electric Communications Business Law in 1985 has given rise to various information/communication systems related activities. This article gives an overview of the trends in automotive information technology.